Índice de masa corporal elevado para la edad como factor de riesgo de menarquia temprana - Calla Rodríguez, Amparito Nélida (2018)
The puberty is a process that includes morphological, physiological and behavioral development, which allows to achieve fertility. In this period, menarche, the most widely used index of sexual maturity, occurs in the girl. In recent years, a tendency to decrease the prevalence of early puberty has been described. Likewise, the prevalence of childhood overweight and obesity ca be noted. Thus, it can be determined if a high BMI for age is a risk factor for early menarche. Materials and methods: A cohort study was carried out with 160 students from ¨Santa Rosa¨ National School of Trujillo, Peru, who met the inclusion criteria. The group exposed was 32 girls who presented high BMI for age. The group not exposed were 128 girls with a BMI not elevated for age. Follow-up section for 12 months to determine if it was presented earlier in the exposed group. Results: In the exposed group, the average age of menarche was 11.31 years. Menarche occurred in 78% of adolescents and did not occur, in 22%. The early menarche was presented in 50%. In the non-exposed group, the average age of menarche was 11.62 years. Menarche occurred in 44% of adolescents and did not occur, in 56%. The early menarche was presented in 19.5%. When applying the Pearson square test, statistically significant differences were obtained (p <0.05). Conclusions: The percentage of girls who experienced early menarche is higher in girls than the high BMI for age, compared to the percentage of girls who experienced early menarche and had a non-high BMI for age, this difference is statistically significant (p < 0.05). Girls who have a high BMI for age are 1.56 times more likely to have early menarche compared to those with a BMI that is not elevated for age